2023
DOI: 10.3389/fphar.2023.1138673
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of a transient receptor potential melastatin 8 (TRPM8) agonist on hyperthermia-induced febrile seizures in infant mice

Abstract: Background: Febrile seizures (FSs) are the most frequent type of seizures in infancy and childhood. Epileptiform discharges (EDs) on electroencephalogram at the time of first FS recurrence can increase the risk of epilepsy development. Therefore, inhibition of EDs is important. Recently, WS-3, a transient receptor potential melastatin 8 (TRPM8) agonist, reportedly suppressed penicillin G-induced cortical-focal EDs. However, the effects of TRPM8 agonists on FSs remain unknown. In this study, we aimed to clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“… 38 Additionally, scientific evidence has substantiated the pain‐relieving properties of menthol in countering chemical stimulation and inflammation through a TRPM8‐dependent mechanism. 39 , 40 , 41 Notably, the absence of analgesic effects of menthol in TRPM8 knockout mice and the complete absence of analgesia induced by WS‐12 (a selective TRPM8 agonist) further support these findings. 42 , 43 The potential antimigraine properties of butterbur may be attributed to the selective activation of the TRPA1 channel by Isopetasin, the primary constituent of its extract, leading to subsequent notable neuronal desensitization.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“… 38 Additionally, scientific evidence has substantiated the pain‐relieving properties of menthol in countering chemical stimulation and inflammation through a TRPM8‐dependent mechanism. 39 , 40 , 41 Notably, the absence of analgesic effects of menthol in TRPM8 knockout mice and the complete absence of analgesia induced by WS‐12 (a selective TRPM8 agonist) further support these findings. 42 , 43 The potential antimigraine properties of butterbur may be attributed to the selective activation of the TRPA1 channel by Isopetasin, the primary constituent of its extract, leading to subsequent notable neuronal desensitization.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, empirical research has demonstrated that the utilization of a high concentration (8%) capsaicin patch yields significant pain alleviation for individuals experiencing postherpes zoster pain and nerve injury pain associated with HIV infection 38 . Additionally, scientific evidence has substantiated the pain‐relieving properties of menthol in countering chemical stimulation and inflammation through a TRPM8‐dependent mechanism 39–41 . Notably, the absence of analgesic effects of menthol in TRPM8 knockout mice and the complete absence of analgesia induced by WS‐12 (a selective TRPM8 agonist) further support these findings 42,43 .…”
Section: Discussionmentioning
confidence: 91%